Phytochemical screening and microbial inhibitory activities of ficus capensis (2012)
Ficus plant components have application in traditional medicine because of the myriad uses they have been subjected to. The ease of application is based on the secondary metabolites this plant contains. The challenges faced by modern medicine especially in the complete cure of microbially-associated diseases through abrupt and unpredictable genetic mutations in the presence of conventional drugs informed the investigation of the microbial inhibitory activities of the stem, root and leaf parts of F. capensis against test disease causing microorganisms. The phenolic, alkaloid and tannin phytochemical fractions were highest in F. capensis bark extract (180, 165 and 155 μg/ml respectively) followed by that contained in the stem extract (100, 90 and 85 μg/ml respectively). While Streptococcus faecalis and Pseudomonas mirabilis were resistant to many different antibiotics (87.5%), they were effectively inhibited by all concentrations of ethanolic F. capensis extracts. The minimum inhibitory concentration of ethanolic extracts ranged from 25% leaf and stem extract concentration respectively (4mm) against S. faecalis and (2mm) against P.mirabilis. All test isolates were 100% susceptible to ethanol extract growth inhibition..